Financial Literacy and Hospitality Values: Their Influence on Financial Behavior of Tourism Sector Employees (Pusat Riset dan Inovasi Nasional, 2026)
The financial well-being of tourism sector employees has become a crucial issue given the industry characteristics of fluctuating income and high turnover rates. This study aims to analyze the influence of financial literacy and hospitality values on the financial behavior of tourism sector employees in Semarang Regency. A quantitative approach with a cross-sectional survey design was employed on 168 employees from hotels, restaurants, and tourist attractions. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results indicate that financial literacy (β=0.412; p<0.001) and hospitality values (β=0.367; p<0.001) have positive and significant effects on financial behavior. Simultaneously, both variables explain 52.7% of the variance in financial behavior. These findings confirm the Theory of Planned Behavior and provide an original contribution through the integration of sectoral values into the financial behavior model. Practical implications include the development of financial education programs based on hospitality values for tourism employees.